ANALISIS PENGATURAN PUTARAN MOTOR INDUKSI 3 FASA DENGAN MENGATUR FREKUENSI MENGGUNAKAN VARIABLE SPEED DRIVE DI PT PDAM TIRTA MANGUTAMA KABUPATEN BADUNG - I Putu Adhe Putra Novantara; I Wayan Arta Wijaya; I Made Suartika (Jurnal SPEKTRUM, 2021)
Along with the increase in technology and knowledge, this increase in the field ofelectric power systems makes the electric power system very developed. Electric motors havevery important benefits in industry. In the operation of the electric machine, it is declared goodwhen viewed from the performance of the motor. The purpose of this research is to find outwhat is the influence of the rotation of a 3-phase induction motor when setting the frequency onthe speed and torque of VSD, as well as the effect of frequency on the amount of torque. Themethod used in this study is to take the rotational speed data measured by VSD and thencompare it with the results of the analysis of the speed and torque calculations. The results ofthe study based on the frequency setting on the VSD Display at PT.PDAM Tirta MangutamaBelusung Area. The results of the VSD settings obtained frequency values of 30 Hz, 35 Hz, 40Hz and 45 Hz. Calculations using the equation of motor rotation speed to frequency, thetheoretical value is compared to 900rpm and from the results of calculations using VSD is nodifference, which is 900rpm. So from these data it can be seen that the data practically showsresults that are in accordance with the theory so that it can be concluded that the performanceof the induction motor is in good condition.